Development of STEM-Based Learning Videos on Escherichia coli Bacteria - Ino Angga Putra; Layyinatul Luyunah; Ospa Pea Yuanita Meishanti (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The purpose of this study was to determine the design and feasibility of STEM-based learning videos with the topic of identifying Escherichia coli bacteria in well water. This type of research is research & development with a 4D development model. but this research focuses on 3 stages, namely define, design, and development. The research subjects were students of the 6th semester of Biology Education Study Program with a total of 7-10 students as respondents. The validation test uses 3 validators who validate the material and media. The data collection instrument used a validation questionnaire and a student response questionnaire. The results of the data obtained indicate that the STEM-based learning video product related to Escherichia coli bacteria in well water is in the